Late Ordovician-Early Silurian trace fossils from the Matapedia Group, Tobique River, western New Brunswick, Canada. II. Additional discoveries with descriptions and comments - Pickerill, R.; Fyffe, L.; Forbes, W. (Atlantic Geology, 1988)
Previous recordings of Late Ordovician-Early Silurian flysch trace fossils (13 ichnogenera, 15 ichnospecies) from slope deposits of the Matapedia Basin at a single site on the Tobique River, western New Brunswick, are supplemented by the addition of 9 newly discovered ichnogenera (12 ichnospecies). These are:- drculichnis montanus, Cruziana problematica, Cruziana cf. stromnessa, Dipt'tchnites ichnosp., Megagrapton irregulare, Monocraterion ichnosp., Phycosiphon incertum, Rusophycus didymus, Rusophycus ichnosp. types A and H,Scolicia ichnosp, and Tuberculichnus ichnosp. The traces are poorly preserved and occur only in low numbers compared to previously documented forms. Nevertheless, the meticulous sampling procedures adopted at the site emphasize the need for detailed collecting, before drawing conclusions regarding diversity models, stratigraphic distribution, etc., of trace fossils. Of these new forms only Diplichnites ichnosp. has previously been recorded from die Matapedia Basin in the partially coeval Lower Silurian Siegas Formation. Tuberculichnus ichnosp. is recorded for the first time in North America. The combined total of 22 ichnogenera (27 ichnospecies) from the Tobique River represents the most diverse ichnocoenosis yet reported from a single ancient slope deposit. The occurrence of several more typically shallow-water ichnogenera (e.g., Cruziana, Diplichnites, Monocraterion and Rusophycus) suggests that, at least in the Early Palaeozoic, caution must be exercised in their utilization as distinctive facies or environmental indicators.